Primer Design of Porcine DNA using Mitochondrial DNA (Cyt b Gene) for Halal Authentication using Polymerase Chain Reaction (PCR) - Rohmah, Siti; Irwansyah, Silvana Lestari; Kasasiah, Ahsanal; Malau, Jekmal (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
The Muslim community has difficulties in determining the halal status of animal-derived items and their derivatives due to their extensive prevalence. Islamic customers are increasingly becoming more selective and are demanding halal certification for culinary goods. Developing a way to identify porcine DNA in goods is of utmost importance. The Cyt b gene is being used to evaluate swine DNA samples by using primer candidates. The process of generating primers utilizing bioinformatics tools, such as NCBI, MegaXI, Primer3Plus, SnapGene Viewer, and Net Primer websites, is utilized to assess and analyze the effectiveness of laboratory research. The study concluded that the primers effectively amplified pig DNA, but they were unsuccessful in amplifying chicken or beef DNA. After conducting in silico experiments, a total of 7 possible primers were generated. The most advantageous pair of primers was identified, which includes the forward primer 5'-AACATCCGAAATCACACCC-3' and the reverse primer 5'-AGAATGATATTTGTCCTCAGGG-3'. The efficacy of these primers was evaluated in a controlled laboratory environment. Results from the laboratory experiments demonstrate that these particular primers have the ability to amplify the Cyt b gene from the Sus scrofa species at a temperature of 58°C, producing a DNA fragment that is 415 base pairs long. DNA sequencing is essential to verify that the amplified DNA band matches to the Sus scrofa Cyt b gene. Keywords: PCR, Porcine, Primer, Cyt b, Halal